Crypto-Secure Data Management for Healthcare : ConV2X 2023 CME Session - Hu , Wei (Blockchain in Healthcare Today, 2024)
Blockchain is a new technology that has attracted a tremendous amount of interest. However, up to now, blockchain has mainly been used to develop decentralized multi-party applications. This presentation describes breakthrough technology that deeply integrates blockchain into the Oracle database. Since virtually all critical data are stored in databases, this makes it possible to implement blockchain in mainstream healthcare and enterprise applications with minimal changes. We will begin by introducing the threats posed by hackers and compromised insiders. Then we will describe how in-database blockchain can protect data against these threats, comparing this against conventional blockchains. Use cases are shared from customers that have adopted this technology. Learning Objectives Understand the concepts behind crypto-security and the threats it addresses Explore the challenges of the adoption of blockchain Learn how database-integrated blockchain can be used to protect critical data against tampering What are the advantages and disadvantages of a database-integrated blockchain? Get an understanding of the types of healthcare data that can be protected using blockchain